Fertility preservation in female patients with hematological disorders - Dan Wu; Huan Shen (BMC, 2022)
Abstract Background The aim of this study was to explore the effectiveness and safety of fertility counseling and fertility preservation using oocyte or embryo freezing prior to chemotherapy or bone marrow transplantation (BMT) in female patients with hematologic disorders. Methods Between 2016 and 2019, 29 patients with hematologic disorders, age range 12-38 years, were given preoperative fertility counseling prior to proposed BMT. Sixteen of these patients, age range 22-38 years, chose to undergo oocyte retrieval followed by ovum or embryo freezing at our Center for Reproductive Medicine. Results As the patients were in urgent need of chemotherapy or BMT, following the random-start controlled ovarian hyperstimulation (COH), an average of 8.2 oocytes were collected. Ten patients had an average of 6.9 oocytes frozen, while 6 patients had an average of 3.2 embryos frozen. There were no intra-operative or postoperative complications, although two patients experienced a blood transfusion reaction of the 11 transfused patients. Conclusion For patients with hematologic disorders, oocyte or embryo freezing prior to chemotherapy or BMT may offer hope for fertility preservation in female patients. However, in order to deliver this, a standardized, feasible, and effective treatment process is needed and should include every aspect of patient selection as well as protocols for ovulation promotion, perioperative management, and postoperative observation.